Respuesta :

znk

Answer:

[tex]\large \boxed{\text{1. a, b, d; 2. a, b, c, d}}[/tex]

Step-by-step explanation:

1.

[tex]\begin{array}{rcl}2x + 12x - 4x & = & 2x(1 + 6 - 2)\\& = & x(2 + 12 - 4)\\& = & 2(x + 6x -2x)\\\end{array}\\\text{The factors are $\large \boxed{\mathbf{2x, x, 2}}$}[/tex]

2.

[tex]\begin{array}{rcl}3ab + 6abc + 12ab + 9ab & = & 3(ab + 2abc + 4ab +3ab)\\& = & 3ab(1 + 2c + 4 +3)\\& = & a(3b + 6bc +12b + 9b)\\& = & 3a(b + 2bc + 4b + 3b)\\\end{array}\\\text{The factors are $\large \boxed{\mathbf{3, 3ab, a, 3a}}$}[/tex]